Barraquer-Simons syndrome: literature review and case report - André Luiz de Araujo França; Luís Alberto de Souza Leite; Jeanine Maria Tejo Caminha; Carlos Lacerda de Andrade Almeida; Ênio Gomes de Araújo; Ernani Coelho Alencar; Rafael Neves de Souza; Jonathan Augusto Vidal de Oliveira; Pedro Flávio de Oliveira Batista (Revista Brasileira de Cirurgia Plástica)
Barraquer-Simons syndrome is a type of lipodystrophy characterized by progressive atrophy of the subcutaneous tissue limited to the upper body. Its involvement is usually symmetrical with craniocaudal evolution, reaching down to the thighs. This syndrome is also known as cephalo-thoracic lipodystrophy or progressive partial lipodystrophy. It is a rare disease of unknown origin that usually manifests at the beginning of the second decade of life and has predominance among women. We report a case and literature review of this rare disease, its therapeutic management, and a comparison with other treatment modalities currently available. During one year and three months follow-up, four sessions of facial fat grafting were performed following the principles of structural fat grafting. The use of this therapeutic modality, improved significantly facial contour, and almost complete disappearance of depressions and irregularities, and preservation were achieved during follow-up time. A number of treatments have been described as effective for lipodystrophy, such as: use of alloplastic materials, autologous grafts, local and microsurgical flaps. Each treatment has advantages and disadvantages. Decision depends on the surgeon's experience, availability of resources, specific materials in each center.